Investigating protein and gene biomarker expression, specifically chemokine (C-X-C motif) ligand 16 (CXCL16), associated with cardiovascular diseases using a combination of in vitro and in vivo techniques - Gahan, Jillian Mary (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2014)
A patient based study was designed to analyze serum concentrations of 10 known inflammatory markers, GM-CSF, IFN-γ, IL-10, IL-12p70,IL-1β, IL-2, IL-6, IL-8, TNF-a and CXCL16 in asymptomatic and symptomatic pre-operative atherosclerotic patients and healthy controls. This was carried out using the eletrochemilluminescence and enzyme-linked immunosorbent assays.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin